O Ministério da Educação (MEC) na Educação de Jovens e Adultos (EJA) : linguagem e discurso - Teixeira, Odinei Inacio (Universidade Federal de São Carlos, 2017)
In this research, we aim to interpret the construction of meanings through the curricular guidelines published in the Curriculum Proposals, in the Notebooks about the EJA and in the Advertising Campaign of 2016, through these officials discourses and the interpretation of their representations on the EJA (Young People and Adults), because "the sense, for AD, is not already fixed a priori as the essence of the words, nor can it be any: there is a historical determination. Still one in-between. (ORLANDI, 2012, p. 27). Thus, the political discourse of the MEC (Ministry of Education) for the EJA constitutes subsidies for the development of educational projects that directly affect this public with the effectiveness or the non-effectiveness of these educational public policies and their respective social consequences. This research is based on the theoretical framework of Discourse Analysis postulated by Pêcheux (1988; 1990) and also on the theoretical aspects postulated by Orlandi (2007a; 2007b; 2007c; 2012). We understand that the ideology of government permeates the MEC and is manifested in the Curriculum Proposals for the EJA, in the Notebooks and in the Advertising Campaign, and according to this movement of meanings, the government ends up perpetuating its dominant ideology with the society, with the subjects and , consequently, in relation to public educational policies. In this way, we have the presence of memory in relation to discourse, that is, interdiscourse. Given the choice of our research object, we adopted the following way from a qualitative research perspective in order to select the statements and images to interpretation, analysis and discussion: a) Visits to the MEC website, specifically, SECADI - Secretariat for Continuing Education, Literacy, Diversity and Inclusion - for the selection of documents, especially curricular guidelines about the EJA; b) Selection of the Curriculum Proposals for the EJA and the notebooks Working with the EJA; c) Visits to MEC profiles on social networks, especially on YouTube and Facebook for the selection of the Advertising Campaign movie (2016) with a recent approach to the EJA; d) Selection and organization of Proposals and Notebooks statements, and of the images obtained through screenshots from the Advertising Campaign for the construction of the discursive sequences in accordance with the selected themes; e) Analysis and interpretation of the discursive sequences supported in our theoretical framework, in order to understand the concepts that belong to the discursive phenomena under study. Our analyzes have made possible to understand that the illusion that government discourse constitutes a stable and closed space for interpretation and its construction of meanings, closes the spaces destined to the profusion of meanings different from those established by the enunciator, and which prevent us from seeing the need of public policies that meet the needs of young and adults learners. In accordance with this position, there is the interdiction of meanings and the construction of the illusion that society, as well as the governmental discourse on the EJA, is also stable and homogeneous. However, the rupture with stability and openness to interpretation show the need for the frequent elaboration of educational public policies that, in fact, meet the needs of the subjects not schooled at the regular age, allowing them a greater autonomy that could potentially be due to schooling.
The Ministry of Education (MEC) in Education for Young People and Adults (EJA) : language and discourse
Keywords: Ministério da Educação; Educação de Jovens e Adultos; Ideologia; Memória; Análise de discurso; Education for Young People and Adults; Ideology; Memory; Ministry of Education; Discourse analysis; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA